Optimizing The ARCS Learning Model as a Post-Pandemi Covid-19 Learning Inovation (Jurnal Scientia Indonesia, 2022)
The impact of the COVID-19 pandemic in Indonesia is enormous, not only on the economy but also on education. Schools are required to close, and students must study at home using online platforms. The implementation of PJJ had an impact on reducing students' learning motivation. Therefore, an innovation is needed so that the learning process in the classroom can continue to run well and can make students motivated and excited to be involved in the learning process. One way to overcome these problems is to apply the ARCS learning model. This study aims to analyze the optimization of the ARCS learning model as a learning innovation after the COVID-19 pandemic. The method used in this study is a qualitative method with a literature study approach or literature study originating from several sources such as books, texts, e-books, and journals which are dominated from the last 2 years relevant to the research. The results of this study are that optimizing the ARCS learning model can increase student learning motivation in the post-COVID-19 pandemic because this model prioritizes learning motivation to improve student learning outcomes. In the learning and learning process, it is very important to practice these four motivational conditions to continue to be maintained so that students' motivation is maintained during the learning and learning process.